Fish Oil in the Treatment of Ulcerative Colitis - C Ó'Moráin; A Tobin; T McColl; Y Suzuki (Canadian Journal of Gastroenterology)
Patients with active ulcerative colitis have increased levels of leukotriene B4 in their rectal mucosa. Eicosapentaenoic acid (EPA) competitively inhibits the cyclo-oxgenase pathway and reduces the formation of cyclo-oxygenase pathway products. EPA is a good substrate for lipoxygenase enzymes and is efficiently converted to leukotriene 85, which is less biologically active. The conversion of EPA to leukotriene B5 is as efficient as that of arachidonic acid to teukotriene B4. Two pilot studies showed benefit of EPA in the treatment of ulcerative colitis. Two of three controlled studies suggest that EPA is more effective than placebo in the treatment of active chronic ulcerative colitis. The mechanism of action is probably reduction of leukotriene B4, but EPA could increase cell and lysosomal membrane stability, or it may exert its effect by reducing interleukin-l. More controlled studies and detailed investigation into the mode of action of EPA are required.